RELIEF MOTIF BURUNG MERAK PADA PESAREAN SUNAN SENDANG DUWUR PACIRAN LAMONGAN: KAJIAN BENTUK, MAKNA DAN ESTETIKA - Sugianto, Herman (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
This study aims to examine the relief of peacock motifs at the gate of Paduraksa I and PaduraksaII tomb complex of Sunan Sendang Duwur Paciran Lamongan which includes (1) visual reliefof peacock motifs, (2) the meaning of relief of peacock motifs, and (3) aesthetic value reliefof peacock motifs. This research uses descriptive qualitative methods with data collectiontechniques, observations, interviews, and documentation. Data analysis using sign analysis ortextual analysis. The results of this study include: visual relief forms of peacock motifs at thegate of Paduraksa I and Paduraksa II at the Sunan Sendang Duwur tomb are ornaments witha floristic style that has undergone Islamization, namely the shape of ornamentation informedof the flora motif into the shape of a peacock animal. The meaning of relief in the tombcomplex of Sunan Sendang Duwur basically gives a picture of how human relations with humans,human relations with nature and the relationship between humans and their Lord. This reliefalso provides a description of the symbols of life that is about courage, knowledge, protection,protection, greatness, strength and justice. This relief also gives us an idea that this tomb complexis a gathering of holy spirits, the final resting place from human to human journey to face Godin another sense that the Sunan Sendang Duwur tomb complex is a sacred/ sacred place, so wemust not carelessly take action or acts that violate the applicable ethics. The aesthetic valuescontained in the reliefs in the tomb complex of Sunan Sendang Duwur, which is a picture ofa journey to holiness and also a picture of the division of nature, that is physical, spiritual andconscience. From the analysis it can be concluded that the relief of the tomb complex of SunanSendang Duwur has a form of ornamentation with a floristic style that is Islamized both interms of visual form, meaning and aesthetic values contained therein connected with Islamicteachings in the form of the teachings about God.